Lipoprotein(a) – Link between Atherogenesis and Thrombosis - Danica Labudovic; Irena Kostovska; Katerina Tosheska Trajkovska; Svetlana Cekovska; Julijana Brezovska Kavrakova; Sonja Topuzovska (Prague Medical Report, 2019)
Lipoprotein(a) – Lp(a) – is an independent risk factor for cardiovascular disease (CVD). Indeed, individuals with plasma concentrations of Lp(a) > 200 mg/l carry an increased risk of developing CVD. Circulating levels of Lp(a) are remarkably resistant to common lipid lowering therapies, currently available treatment for reduction of Lp(a) is plasma apheresis, which is costly and labour intensive. The Lp(a) molecule is composed of two parts: LDL/apoB-100 core and glycoprotein, apolipoprotein(a) – Apo(a), both of them can interact with components of the coagulation cascade, inflammatory pathways and blood vessel cells (smooth muscle cells and endothelial cells). Therefore, it is very important to determine the molecular pathways by which Lp(a) affect the vascular system in order to design therapeutics for targeting the Lp(a) cellular effects. This paper summarises the cellular effects and molecular mechanisms by which Lp(a) participate in atherogenesis, thrombogenesis, inflammation and development of cardiovascular diseases.